Prediction of difficult airway management in traumatic cervical spine injury: influence of retropharyngeal space extension - Lee J; Kim JS; Kang S; Shin YS; Doo AR (Dove Medical Press, 2019)
Jeongwoo Lee,1,2,* Jeong Seob Kim,1 Sehrin Kang,1 Yu Seob Shin,2,3,* A Ram Doo1,2 1Department of Anesthesiology and Pain Medicine, Chonbuk National University Medical School, Jeonju, South Korea; 2Research Institute of Clinical Medicine of Chonbuk National University-Biomedical Research Institute of Chonbuk National University Hospital, Jeonju, South Korea; 3Department of Urology, Chonbuk National University Medical School, Jeonju, South Korea *These authors contributed equally to this work Background: Retropharyngeal hematoma following cervical spine trauma may lead to life-threatening upper airway obstruction and difficult airway management. This retrospective study was performed to investigate whether the extension of retropharyngeal space (RPS) was associated with difficult intubation by direct laryngoscopy in traumatic cervical spine injury.Patients and methods: Sixty-two patients who had undergone direct endotracheal intubation under general anesthesia for cervical spine surgery were retrospectively identified. Laryngoscopic grade by Cormack–Lehane (C-L) classification was collected; grade 1 or 2 was categorized as easy laryngoscopy, whereas grade 3 or 4 was categorized as difficult laryngoscopy. In these patients, RPS thickness and the proportions of RPS to the vertebral bodies were measured at the 2nd, 5th and 7th cervical spine levels using magnetic resonance imaging (MRI) of the cervical spine. Measures of RPS were compared between easy and difficult laryngoscopy. Relationships between measures of RPS and difficult laryngoscopy were analyzed with logistic regression analysis.Results: RPS thickness at C2 was significantly greater in difficult laryngoscopy (median 14.29 mm, IQR: 9.75–18.04) than easy laryngoscopy (median 5.10, IQR: 4.33–5.94, p<0.001). Proportion of RPS to the C2 vertebral body were significantly higher in difficult laryngoscopy than in easy laryngoscopy (p<0.001). RPS thickness and the proportion of RPS to the vertebral body were significantly associated with difficult laryngoscopy (OR=2.13, 95% CI: 1.38–3.30; p<0.001 and OR=1.13, 95% CI: 1.05–1.21; p<0.001, respectively).  Conclusion: RPS extension at the upper cervical spine level is associated with difficult direct laryngoscopy in traumatic cervical spine injury. Keywords: cervical spine injury, difficult airway, endotracheal intubation, retropharyngeal space